Women and the criminal justice system - Van Wormer, Katherine S.; Bartollas, Clemens (Boston Prentice Hall, 2011)
Synopsis: Women and the Criminal Justice System, third edition, has been thoroughly updated to reflect the continuing impact of globalization and economic insecurity on the criminal justice system, as well as the increasing feminization of poverty. The text examines the various roles of women in the criminal justice system within a social context in which women are oppressed. The authors introduce students to the empowerment approach, emphasizing gender and ethnic diversity along with the strengths of oppressed people, especially women of color. A wide range of issues are covered, including the rate of early childhood sexual abuse, victimization in female inmates, priest abuse of girls, female inmate rape by male prison guards, and obstacles for women lawyers achieving partnerships in their firms. The text examines three roles of women in criminal justice: Women as victims of crimes; Women as criminals convicted and sentenced for crimes; Women as workers in various agencies in the criminal justice system.
Theoretical perspectives on women and the criminal justice system -- Women in crime -- Feminist theory and research -- Delinquency across the life span -- Women, substance abuse, and criminal justice -- The prison environment -- Restorative justice for female victims and offenders -- Rape -- Wife and partner abuse -- Women's victimization : global perspectives -- Women in law enforcement -- Women in the legal profession -- Women in corrections -- Summary and trends for the future.
Keywords: Sex discrimination in criminal justice administration -- United States; Women -- Drug use -- United States; Female offenders -- United States; Women prisoners -- United States